Anti-inflammatory Activity Guided Fractionation of Aerial Parts of Clematis gouriana Roxb. ex DC. Issue 5 (3rd September 2022) - Kalia, Ritu; Jachak, Sanjay M.
Abstract: Clematis gouriana Roxb. ex DC. also known as Indian Traveler's Joy is used in different regions of India for curing skin infections, cuts and wounds. The study was performed on 70% methanol extract of C. gouriana aerial parts and its n-hexane, ethyl acetate and n-butanol fractions. The in vitro and in vivo anti-inflammatory potential was evaluated using inhibition of NO production in LPS-stimulated RAW 264.7 macrophages cell line and carrageenan-induced rat paw edema model in vivo, respectively. All the extracts and fractions exhibited concentration-dependent inhibitory effects. It was found that ethyl acetate fraction was the most potent fraction showing 77.24±0.71% inhibition of NO release at 100 μg/mL concentration. The ethyl acetate fraction of C. gouriana also showed significant anti-inflammatory activity in the carrageenan-induced rat paw edema model at a dose of 400 mg/Kg. Further, the phytochemical investigation of the bioactive ethyl acetate fraction led to isolation of five compounds belonging to phenolics and flavonoids type of natural products. GRAPHICAL ABSTRACT: UF0001